2012
DOI: 10.1080/09500782.2011.609281
|View full text |Cite
|
Sign up to set email alerts
|

‘I’m going to split you all up’: examining transitions to group/pair work in two primary English classrooms

Abstract: Lesson transitions are important units for analysis not only for establishing the presence of group/pair work but also for examining the contextual conditions for small-group learning. Scholars have suggested that the 'open' or 'closed' contextual conditions set up through the teacher's use of language to introduce group/pair work influence the quality of pupil's talk and interthinking, i.e. the use of language for thinking together and collectively solving problems. The nature of transition, however, has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…In the UK, Mercer (2000) suggests that classrooms should be organized for inclusion based on the understanding that individual development occurs through active participation in a community, or network of interthinkers (see Vygotsky, 1978). This is a learning community in which more experienced community members act as ‘discourse guides’, who model ways of using language for thinking collectively (Lwin, Goh, & Doyle, 2012; Mercer, 2000). In Hong Kong, Cheng, Lam, and Chan (2008) found that ‘the quality of group processes played a pivotal role because both high and low achievers were able to benefit when group processes were of high quality’ (p. 205).…”
Section: Thematic Discussion: Inclusive Classroom Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the UK, Mercer (2000) suggests that classrooms should be organized for inclusion based on the understanding that individual development occurs through active participation in a community, or network of interthinkers (see Vygotsky, 1978). This is a learning community in which more experienced community members act as ‘discourse guides’, who model ways of using language for thinking collectively (Lwin, Goh, & Doyle, 2012; Mercer, 2000). In Hong Kong, Cheng, Lam, and Chan (2008) found that ‘the quality of group processes played a pivotal role because both high and low achievers were able to benefit when group processes were of high quality’ (p. 205).…”
Section: Thematic Discussion: Inclusive Classroom Environmentsmentioning
confidence: 99%
“…In FoLEs, the essential requirement for group/pair work is ‘that the balance of ownership and control of the work shifts towards the pupils themselves’ (Blatchford, Kutnick, Baines, & Galton, 2003, p. 155). This partial transfer of control requires teachers to use language that encourages students to verbalize their own recondite thinking processes (Lwin et al, 2012). Interactions of this quality create and sustain FoLEs, where students feel empowered and encouraged to participate.…”
Section: Thematic Discussion: Inclusive Classroom Environmentsmentioning
confidence: 99%
“…In school settings, generally what counts as successful collaborative group work tends to be defined by the overall product or artifact created rather than by group processes. Furthermore, it is assumed that in small groups, collaboration will happen naturally (Lewin et al., 2012). By the time children have produced a final artifact, the processes, social positions, and social representations of meaning and understanding ‘have disappeared, become invisible in, and [are] unrepresented by the actual piece handed in for evaluation’ (Roth, 1997, p. 298).…”
Section: Discussionmentioning
confidence: 99%
“…Third, due to low English language proficiency, EFL students may keep quiet and shy, and thus avoid speaking up in class for fear to be rebuked, ridiculed, or punished by teachers or laughed at by classmates when they make mistakes. In the same line, lack of appropriate and effective professional training and qualifications may hinder teachers from feeling comfortable, confident, and self-efficacious enough to implement the VSA in their respective classrooms (Chen &Goh, 2011).…”
Section: Potential Challenges Of the Vsamentioning
confidence: 99%